Risk Factors for Stunting Among Children Aged 6–24 Months in Uluere Subdistrict, Bantaeng Regency, Indonesia - Gione Giandito; Arman Arman; Hasriwiani Habo Abbas; Fatmah Afriyanti Gobel; Nur Ulmy Mahmud (Window of Health : Jurnal Kesehatan, 2026)
Stunting remains an important child health problem in Indonesia, particularly during the first 1,000 days of life. This study aimed to identify factors associated with stunting among children aged 6–24 months in Uluere Subdistrict, Bantaeng Regency. A frequency-matched case-control study was conducted by child age group and sex. Child age and sex were subsequently retained as adjustment variables in the multivariable logistic regression to account for the matching design. Cases were children with a length-for-age z-score (LAZ) <−2 SD, whereas controls had LAZ ≥−2 SD based on WHO standards. The study included 69 cases and 136 controls. Child age was retained as an adjustment variable, while sex was included as a prespecified covariate in multivariable logistic regression. Recent illness history showed the strongest statistical association with stunting. This can be seen in the statistical analysis odds ratio for stunting (aOR 4.23; 95% CI 1.91–9.36; p<0.001), followed by low birth weight (aOR 3.59; 95% CI 1.43–8.99; p=0.006) and uncovered household waste bins (aOR 2.01; 95% CI 1.06–3.80; p=0.033). Family food consumption was associated with lower odds of stunting (aOR 0.45; 95% CI 0.20–0.99; p=0.049), although this estimate was close to the significance boundary. The final model demonstrated acceptable discrimination (AUC = 0.722), although its explanatory power remained modest (Nagelkerke R² = 18.6%). These findings support closer monitoring of children with low birth weight, morbidity prevention, improved household waste management, and age-appropriate feeding support, without implying causal relationships.